Methods and Values of Prophet Ibrahim’s Child Education in The Qur’an Surah aṣ-Ṣāffāt Verses 85-113 - Amrin Amrin; Adi Priyono; Nurrahmaniah Nurrahmaniah; Supriyanto Supriyanto (Islamic Religious Education Departement, 2023)
The impact of globalization causes various kinds of negative behavior and actions in early childhood, causing a degradation of morality and religiosity. The research objective was to determine the concept of Islamic education and the methods and values developed by the Prophet Ibrahim in the education of children in QS aṣ-Ṣāffāt verses 85-113. This study uses a linguistic (philological/semantic) approach regarding the verses of the al-Qur'an Surah Aṣ-Ṣāffāt Verses 85-113, with the type of library research. The primary source in this research is the al-Qur'an surah aṣ-Ṣāffāt verses 85-113, and the secondary sources include the interpretation books, such as: